INTEGRASI PERILAKU DAN KOMPETENSI KEPEMIMPINAN TRANSFORMASIONAL DALAM MENUNJANG KINERJA ORGANISASI ( Studi organisasi Kantor “x”) - kristiyo, albertus; Dwi Putranti , Honorata Ratnawati (Transformasi: Journal of Economics and Business Management, 2024)
Abstract. This case study explores the influence of transformational leadership style in facilitating innovation and synergy in an institution. Through the analysis of conceptual relationship diagrams among various operational elements within the organization, this study demonstrates how transformational leadership impacts decision-making processes, innovation, and competency enhancement. In this context, leadership acts not only as a decision maker but also as a motivator inspiring active participation and commitment from team members. The emphasis on consultation and coordination in decision-making illustrates the implementation of democratic practices supporting a collaborative and inclusive work environment. Furthermore, the study identifies innovation as a central pillar driving the institution to adapt to changes and meet the dynamic market needs. Initiatives such as the implementation of modern technology and new approaches in human resource management are illustrated as key components in the organization’s innovative strategy. The findings of this case study underscore that transformational leadership is effective in triggering organizational growth and sustainability by integrating innovation and collaboration. The implications of these findings provide important insights for other institutional leaders in designing leadership strategies that not only direct the organization to achieve its targets but also ensure ongoing adaptation and growth in a continually changing environment. This study offers valuable contributions to the literature on organizational leadership, particularly in the context of institutions operating in the era of globalization and digital transformation.